Innovations in Intelligent Machines - 1 - Chahl, Javaan Singh; Mizutani, Akiko; Sato-Ilic, Mika (Studies in Computational Intelligence,, 2007)
This book includes a collection of chapters on the state of art in the area of intelligent machines. This research would provide a sound basis to make autonomous systems human-like. The contributions include: An introduction to intelligent machines Supervisory control of multiple UAVs Intelligent autonomous UAV task allocation UAV path planning Dynamic path planning Routing in UAVS State estimation of micro air vehicles Architecture for soccer playing robots Robot perception Application engineers, scientists and researchers will find this book useful.